2016
DOI: 10.18632/oncotarget.9839
|View full text |Cite
|
Sign up to set email alerts
|

Novel cancer stem cell targets during epithelial to mesenchymal transition in PTEN-deficient trastuzumab-resistant breast cancer

Abstract: Continued use of trastuzumab in PTEN-deficient HER2+ breast cancer induces the epithelial-to-mesenchymal transition (EMT), transforms HER2+ to triple negative breast cancer, and expands breast cancer stem cells (BCSCs). Using cancer cell lines with two distinct states, epithelial and mesenchymal, we identified novel targets during EMT in PTEN-deficient trastuzumab-resistant breast cancer. Differential gene expression and distinct responses to a small molecule in BT474 (HER2+ trastuzumab-sensitive) and the PTEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
0
41
1
Order By: Relevance
“…vinca alkaloids, taxanes, camptothecins [ 92 ] which have fewer side effects than synthetic ones. Recently, a new natural compound sulforaphane was identified, which eliminates cancer stem cells in many cancer types [ 93 95 ]. Multiple survival pathways make trouble for anticancer drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…vinca alkaloids, taxanes, camptothecins [ 92 ] which have fewer side effects than synthetic ones. Recently, a new natural compound sulforaphane was identified, which eliminates cancer stem cells in many cancer types [ 93 95 ]. Multiple survival pathways make trouble for anticancer drug discovery.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MEOX1 is related to signaling pathway. One study showed that HER2 signaling regulated MEOX1 in HER2 + breast cancer [9].Another report demonstrated that MEOX may control Bapx1 expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, MEOX1 affected the progression of triple-negative breast cancer [7,8]. In addition, siRNA knockdown inhibits breast cancer cell frequency and the growth of tumor through down-regulation of MEOX1 [9]. However, the clinicopathological significance of MEOX1 in EEA remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Mutation in MEOX1 gene was involved in Klippel-Feil syndrome - a skeleton disease with abnormal fusion of two or more cervical vertebras [45]. In a recent study, MEOX1 was proved to be a key molecular target that regulating breast cancer stem cells and was associated with worse clinical survival in BC patients [46]. Given the information above, we infer that rs7808138 and rs4793019 are not only BMD GWAS-associated SNPs but also potential novel SNPs associated with BC.…”
Section: Discussionmentioning
confidence: 99%